Manual differential leukocyte count in the presence of large immature cells detected by automated hematology analyzer - Goyal, Binita; Rup Shrestha, Akshunna (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Large immature cells (LICs) are myeloid or lymphoid cells normally present in bone marrow which may be released in peripheral blood in various conditions. The automated hematology analyzers though have good correlation with microscopy for mature cells, give flag messages when immature cells are present and manual microscopy remains the reference method. The objective of this study was to find types of immature cells comprising LICs and see correlation of automated and manual Differential leukocyte count (DLC) in presence of such cells. Methods: This cross-sectional study was conducted in the Central Clinical Laboratory, College of Medical Sciences, after ethical approval. A total of 100 EDTA-anticoagulated blood samples with LIC >3% on automated DLC using the Horiba Yumizen H550 analyzer were included. Repeat CBC samples and leukopenic cases without automated DLC were excluded. CBC and DLC parameters including Hb, TLC, platelet count, and differential counts were recorded. Pearson correlation was used to assess relationship, with p<0.05 considered significant. Results: Total leukocyte count ranged from 790 to 479190/cumm. Myeloblasts were seen in 6%, promyelocytes in 6%, myelocytes in 41%, metamyelocytes in 73%, bands in 84%, lymphoblasts in 2%, atypical lymphocytes in 30% and atypical monocytes in 5%. There was strong correlation between automated and manual DLC for neutrophils, lymphocytes and eosinophils, fair correlation for monocytes (p<0.001) and no correlation for basophils (p=0.175). Conclusions: Manual microscopy is required to evaluate all the cases in presence of LIC more than reference range.